The Cost-Oriented Stochastic Assembly Line Balancing Problem: A Chance Constrained Programming Approach - Foroughi, Ahad; Gökçen, Hadi; Tiacci, Lorenzo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
In recent years, the increase in industry competition has caused costs of production to become a critical success factor. A considerable proportion of manufacturing activities and costs are devoted to the assembly of products. Therefore, in successful assembly line production systems, a reduction in production costs is a necessity. From an economic point of view, cost-oriented objective for assembly line balancing should be considered. This issue is addresses Cost-oriented Assembly Line Balancing (CALB) problem. To fill a gap in the existing literature on stochastic version of CALB problem. Chance constrained programing model has been proposed in this paper and to linearize the model, two methods have been adopted from Ağpak and Gökçen [1] : an approximation method, and an exact one. The resultant models have been tested on different problems in order to assess their effectiveness. A comparative study has also been conducted for the cost and time-oriented versions of the problem.